Thermal degradation of both latex and latex cast films forming membranes - Combined TG/FTIR investigation - Agostini, D. L. S. [UNESP]; Constantino, C. J. L. [UNESP]; Job, Aldo Eloizo [UNESP] (Springer, 2008)
Latex collected from natural rubber trees forming membranes can be used as biomaterials in several fields being the temperature a key parameter. Thermogravimetry (TG) coupled to Fourier transform infrared spectroscopy (FTIR) is a useful technique to investigate the thermal degradation of both latex and cast films (membranes), wich were obtained from Hevea brasiliensis (RRIM 600 clone) and used without stabilization. The membranes were prepared by casting the latex onto a glass substrate at 65 degrees C for 6 h. The thermal degradation was followed by FTIR spectra acquisition along the process, allowing the identification of the gaseous components evolved upon the thermal treatment. According to TG measurements, the main processes of thermal degradation of the latex and membranes occur at three temperature intervals for both.
Keywords: latex; natural rubber membranes; TG/FTIR coupling; thermodegradation